Determinan Kepatuhan Pengunjung Dalam Protokol Kesehatan Pencegahan Covid-19 Di RSUD Deli Serdang Lubuk Pakam - Nurcahaya Putri Nasution; Asima Sirait; Frida Lina Tarigan (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Compliance with washing hands, wearing masks, and maintaining distance (3M) are prerequisites for breaking the chain of transmission of Covid-19. The purpose of this study was to determine the determinants of visitor compliance in the Covid-19 prevention health protocol at Deli Serdang Lubuk Pakam Hospital. This study used a cross sectional design. The population of this study were all visitors with an average of 4,249 people per month. The sample size was 366 people, taken using accidental sampling. The primary data type uses a questionnaire sheet. Data analysis used chi-square test and multiple logistic regression. The results showed that the significant variables included p value = 0.000 for knowledge (p value = 0.000), motivation (p value = 0.000). The most dominant variable related is family support with a beta coefficient of 2.705. In conclusion, there is a relationship between knowledge, motivation and family support with visitor compliance in the Covid-19 prevention health protocol. People are expected to wear masks when leaving the house, wash their hands with soap, keep their distance from people, avoid crowds and carry hand sanitizer when traveling.